Surgery in the Multimodal Management of Gastric Cancer - Manzoni, Giovanni; Roviello, Franco; Siquini, Walter; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2012)
Although there has been a slow but steady decrease in incidence, gastric cancer remains the second leading cause of cancer death worldwide. Several aspects of the oncological and surgical management are still controversial and so gastric cancer represents a challenge for the surgeon. This book aims to delineate the state of the art in the surgical and oncological treatment of gastric cancer, describing the new TNM staging system, the extent of visceral resection and lymphadenectomy focusing on the different open and minimally invasive surgical techniques and discussing intraoperative chemohyperthermia and neoadjuvant and adjuvant treatment. Operative endoscopy and endoscopic ultrasonography are also discussed, as these now have an important role in both diagnostic work-up and palliative care of gastric cancer patients. Only a multidisciplinary approach involving the surgeon, gastroenterologist, and oncologist can produce the comprehensive and integrated overview that today constitutes a winning strategy for the optimization of results.What we hope we have achieved is a flexible, up-to-date, exhaustive publication, rich in illustrations and consistent with evidence-based medicine.
Keywords: Medicine; Gastroenterology; Oncology; Cancer -- Surgery; Surgery; Abdomen -- Surgery; Medicine & Public Health; Surgery; Abdominal Surgery; Oncology; Surgical Oncology; Gastroenterology